Rethinking Border Enforcement, Permanent and Circular Migration - Arnab K. Basu; Nancy H. Chau; Brian Park (Institute of Labor Economics (IZA), 2021)
Canonical models of migration feature border enforcement as a strategy to contain undocumented immigration by effectively exacting a mobility cost. This paper revisits the role of border enforcement policy in a task-based model of the labor market where employers simultaneously hire circular migrants to take temporary tasks at low wages, in addition to permanent and native workers who perform complementary tasks at the efficiency wage. We show that stricter border enforcement is effectively a tax on temporary employment, and as such it incentivizes the reallocation of work along the task spectrum. Employersâ exteuro™ dependence on low-wage transient work force diminishes, while more migrants prefer permanent migration, with labor market tightness consequences that favor both native and migrant workers. We explore the empirical implication of this finding, by investigating the pattern of spousal reunion among Mexican agricultural workers in the United States subsequent to major border enforcement reforms in the 1990â exteuro™s.
Keywords: F22; J61; J68; 330; labor shortages; family migration; circular migration; border enforcement